2002
DOI: 10.1637/0005-2086(2002)046[0198:eoacce]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Commercial Competitive Exclusion Culture on Reduction of Colonization of an Antibiotic-Resistant Pathogenic Escherichia coli in Day-Old Broiler Chickens

Abstract: One-day-of-age broiler chickens were administered a commercial competitive exclusion (CE) product and then challenged by three different methods with an Escherichia coli O78:K80 that was pathogenic for poultry and resistant to six antibiotics. Three challenge methods were used on 2-day-old broilers: direct challenge, precolonized seeder, and instant seeder. Direct challenge was accomplished by administering the challenge E. coli per os. The precolonized seeder challenge had two chicks that had received the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Although different animal trials (with Broilact versus Aviguard, 5 versus 14 days of follow-up, and various challenge strains) were set up, our results are in line with the overall reduction in the amounts of E. coli (35,39) or ESBL-producing E. coli (34) observed in broilers treated by use of the competitive exclusion strategy. In our study, both transmission and excretion were calculated and shown to be reduced by competitive exclusion, whereas previous studies analyzed only E. coli colonization rates, which did not allow a direct comparison of different parameters.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although different animal trials (with Broilact versus Aviguard, 5 versus 14 days of follow-up, and various challenge strains) were set up, our results are in line with the overall reduction in the amounts of E. coli (35,39) or ESBL-producing E. coli (34) observed in broilers treated by use of the competitive exclusion strategy. In our study, both transmission and excretion were calculated and shown to be reduced by competitive exclusion, whereas previous studies analyzed only E. coli colonization rates, which did not allow a direct comparison of different parameters.…”
Section: Discussionsupporting
confidence: 82%
“…This approach has proved to be effective in terms of limiting colonization of broilers with pathogenic E. coli strains (35,38,39) as well as Salmonella (40). Similar results were obtained in studies to control colonization with and shedding of different nonpathogenic ESC-resistant E. coli strains in the ceca of broilers (34).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This allows environmental bacteria to play a larger role in seeding the intestinal tract of the commercial broiler chick [1,2]. Many commercial poultry companies use a built up litter system, meaning that the bacteria left in the litter from the resistance [20][21][22][23][24][25] and modulation of inflammation [26][27][28][29][30][31][32]. It is imperative that chicks receive autogenous pioneer colonizers to mediate the development of a healthy intestinal microbiome essential for optimal flock performance.…”
Section: Introductionmentioning
confidence: 99%